Assessing the Forecast Properties of the CESifo World Economic Climate Indicator: Evidence for the Euro Area - Oliver Hülsewig; Johannes Mayr; Stéphane Sorbe (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2007)
This paper evaluates short-term forecasts of real GDP in the Euro area derived from the CESifo Economic Climate indicator (WES) in terms of forecast accuracy. We compare the forecast properties of the WES with those of monthly composite indicators. Considering the WES is interesting because (i) it is exclusively based on the assessment of economic experts about the current economic situation, and (ii) it is timely released within the quarter on a quarterly basis. The empirical analysis is carried out under full information, which means that the competing monthly indicators are known for the entire quarter, and under incomplete information. Our findings exhibit that the forecast power of the WES is comparatively proper.
Keywords: C22; C53; 330; CESifo World Economic Survey; business-cycle forecasts; bridge models; out-of-sample forecast evaluation